Changes in Antarctic surface conditions and potential for ice shelf hydrofracturing from 1850 to 2200 - N. C. Jourdain; C. Amory; C. Amory; C. Kittel; C. Kittel; G. Durand (The Cryosphere)
A mixed statistical–physical approach is used to emulate the spatio-temporal variability of the Antarctic Ice Sheet surface mass balance and surface melt rates of a regional climate model. We demonstrate the ability of this simple method to extend existing regional climate simulations to periods, scenarios, or climate models that were not originally simulated. This method is useful to quickly populate ensembles of surface mass balance and melt rates, which are needed to constrain ice sheet model ensembles. Here we apply this method to estimate (i) the changes in Antarctic surface mass balance over 1850–2200 and the associated effect on sea level and (ii) the changes in potential for ice shelf hydrofracturing.